2018
DOI: 10.14814/phy2.13941
|View full text |Cite
|
Sign up to set email alerts
|

Imoxin attenuates LPS‐induced inflammation and MuRF1 expression in mouse skeletal muscle

Abstract: The double‐stranded RNA‐dependent protein kinase (PKR) contributes to inflammatory cytokine expression and disease pathogenesis in many conditions. Limited data are available on the efficacy of the PKR inhibitor imoxin to prevent lipopolysaccharide (LPS)‐induced inflammation in skeletal muscle in vivo. The aim of this study was to evaluate the effect of imoxin, a PKR inhibitor, on inflammatory and atrophy signaling in skeletal muscle in response to an acute inflammatory insult with LPS. Six‐week old C57BL/6J m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…All experiments were performed on animals of 4 months of age. In the LPS-induced inflammatory model, muscle inflammation induced was performed a described previously [54], except that 15 µg/kg of GW501516 was injected subcutaneously 2 h and 24 h prior LPS injection. In the carrageenan-induced inflammatory model, carrageenan solution (3%) at 10 mg/kg body weight was injected into the hindlimb muscle.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…All experiments were performed on animals of 4 months of age. In the LPS-induced inflammatory model, muscle inflammation induced was performed a described previously [54], except that 15 µg/kg of GW501516 was injected subcutaneously 2 h and 24 h prior LPS injection. In the carrageenan-induced inflammatory model, carrageenan solution (3%) at 10 mg/kg body weight was injected into the hindlimb muscle.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Immediately after decapitation, the gastrocnemius was extracted and flash-frozen with liquid nitrogen then stored at −80°C until the time of analysis. Western blot analysis followed previously described methods (Valentine et al, 2018 ). Approximately 15–25 μg of protein were separated by 4–15% gradient Stain-Free Criterion TGX gel electrophoresis (Bio-Rad, Hercules, CA, USA), and transferred onto a polyvinylidene difluoride membrane (MilliporeSigma, Burlington, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…We also found that Aspirin significantly inhibited the expression of autophagy-related proteins PINK1, BNIP3, LC3B and ATG7 in denervated skeletal muscle, suggesting that Aspirin inhibited the activity of autophagy lysosomal hydrolysis system. Studies have shown that inflammation can activate the expression of E3 ubiquitin ligases MuRF-1 and MAFbx (28,29). We found that the expression of inflammatory factors IL-6, IL-1 β and TNF-α in denervated skeletal muscle was significantly increased.…”
Section: Discussionmentioning
confidence: 64%